Analisis Sifat Tanah Lempung Lunak yang Di Stabilisasi Dengan Limbah Ban Karet dan Fly Ash - Hasrullah; Hasan Bisri (Indonesian Society of Applied Science, 2026)
Soft soil in construction is often a problem. This is because the bearing capacity of the soil is very low. Various soil improvement methods have been developed, one of which is the soil stabilization method. This study aims to investigate the effect of the addition of waste rubber tires and fly ash as stabilizer materials on changes in the physical and mechanical properties of soft clay soil. In addition, the effect of the length of curing of the soil mixture with stabilizer was also observed. After identifying the clay soil locally, the clay soil was mixed with stabilizer materials at several percentages (5%, 10%, 15% and 20%), which were then cured for 7, 14, and 28 days before testing the physical and mechanical properties. The results revealed that rubber tire powder plus fly ash mixed in soft clay soil had a positive effect on the physical and mechanical properties of the soil. The results of the consistency limits test showed a decrease in moisture content by 53.23% and the plasticity index (PI) value of the soil by 27.32% from its original condition. This decrease depends on the length of the soaking period. In addition, the CBR test results also increased significantly. The largest data value was obtained at 20% stabilizer mixing with 28 days of curing time by 10.32%. This shows that rubber tire powder and fly ash can work well as a binder (pozzolan) because they can bind the soil so that the carrying capacity of the soil increases.